Interstices: teaching representations about the pedagogical integration of ICT (Praxis Educativa, 2017)
In Argentina, the relationship between Information and Communications Technology (ICT) and education get renewed strength from digital inclusion policies, whose main exponent is the program ConectarIgualdad. It is our purpose to examine teachers` representations in relation to these processes, their modes of use and digital appropriation, pedagogical and  political-ideological models that hold and organize them, the skills that they recognize and, in general, the weave of perceptions which make intelligible increasingly complex techno educational environments. In this sense, the field of communication/education links with a critical pedagogy that challenges teachers not as technicians, but as a public intellectuals, capable of promoting critical engagement trough different records of meaning that turn into pedagogical practices inside and outside the classroom.
Keywords: ICT; education; educational performances; digital appropiation; techno-communication skills.